INVESTIGATING THE INFLUENCE OF PARENTS ON UNIVERSITY STUDENTS’ CAREER CHOICES IN BANTEAY MEANCHEY, CAMBODIA - Kol Sovanvatthana; Lim Kim Eav; Chea Leanghuor; Hang Makara (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study seeks to investigate the influence of parents on university students’ career choices in the province of Banteay Meanchey, Cambodia. Cambodian parental cultures often provide valuable guidance and support, significantly shaping their children’s decisions. Their influence helps students make informed choices that align with their parents’ perspectives and interests, influencing both their university majors and future careers. In this particular scenario, parental influence on university students’ career choices is generally acknowledged. However, uncertainties may exist regarding the influence and the specific experiences students have had with their parents. In an effort to accomplish the objectives of this research study, the multifaceted direct influences, personal experiences, and financial support contributing to the nature of parental influence on children are investigated. The goal is to uncover new findings in the digital age that may differ from previous studies. The researchers optimistically hope that these new insights and useful resources will be beneficial tools for future studies.